Alone, not lonely : a guide to embracing solitude - Kok, Joemin Jie Ming (2017)
Living in a world of social connectivity has caused us to lose our ability to connect with ourselves. A “friendless” individual will often be seen as a lonely, isolated being. The concept of aloneness has been embraced, yet the practice and reality of being alone have been frowned upon. This project explores Singaporean millennials’ perception of aloneness and proposes a step by step guide on how to appreciate it as a way of life towards improving physical, mental and emotional health. By emphasising the need to focus on oneself through being comfortable alone, it can be a powerful method for achieving deep introspection, self-love and exponential personal growth. This project aims to firstly eradicate the fear of judgement of being seen alone and introduce the concept of the Spotlight Effect. Through a combination of interactive activities and experiential installation, ways of encountering aloneness will be explored and will encourage the audience to be part of the solo discovery experience.